A Love of UIQ - Guattari, Felix (Book collections on Project MUSE., 2016)
Throughout a large part of the 1980s, Félix Guattari, known for his collaborations with Gilles Deleuze and his experimental and groundbreaking practices in psychotherapy, decides to shift his experimental work into a different medium of artistic and creative thought practice: the world of science fiction. Part self-analysis, part cinematic expression of his theoretical work, Guattari's screenplay merges his theoretical concepts with his passion for comic books, free radio movements, and film. So begins Guattari's journey to write a screenplay wherein a group of squatters makes contact with a superior intelligence coming from the infinitely small Universe of the Infra-quark (UIQ). Guattari worked feverishly on his film, attempting to secure a budget, traveling to Hollywood, and enlisting the help of American screenwriter Robert Kramer. But the film would never see the light of day. Through the important archival work of artists, Silvia Maglioni and Graeme Thomson, Guattari's script is now published here, for the first time in English.